Zero trust in cloud identity and access management: A review of models, advantages and limitations - Cordova Urbina, Daily Ashley (2025)
The growing adoption of cloud computing and digital environments has increased the frequency of attacks and the likelihood of unauthorized access, against which traditional identity and access management (IAM) models prove insufficient. In this context, the Zero Trust approach emerges as a more robust alternative that redefines security. The aim of this research was to analyze IAM models applied to cloud computing under the Zero Trust framework, as well as to identify their advantages and limitations. Using the PRISMA methodology, a search was conducted across three databases, and after applying inclusion criteria, 22 manuscripts were analyzed. The results reveal 15 IAM models based on Zero Trust that integrate artificial intelligence, blockchain, and dynamic access control, offering enhanced security in areas such as 5G, IoT, cloud, and healthcare. Nevertheless, limitations remain regarding complexity, costs, scalability, and privacy. In conclusion, these models not only strengthen security but also represent a line of inquiry and development aimed at reformulating resource protection across diverse sectors.